Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera: Ensifera: Stenopelmatoidea) XXVII: One new species of the genus Ultragryllacris Gorochov & Dawwrueng, 2015 from China - Luo, Ting; Bian, Xun (Zootaxa, 2025)
The Chinese Ultragryllacris is further studied. Ultragryllacris nigrifrontis sp. nov. as a new species is described and illustrated. It differs from Ultragryllacris chandra Dawwrueng, Gorochov & Suwannapoom, 2023 in the coloration of the pronotum, the shape of male ninth abdominal tergite and the female subgenital plate. All the specimens are deposited in Guangxi Normal University.